(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Severe Acute Respiratory human Coronavirus 2 (SARS-hCOV 2) infection which began in December 2019 has rapidly disseminated worldwide due to non-availability of anti-viral treatment or vaccine, no knowledge of virus-human interaction, lack of prognostic factors for stages of illness and ability of hCoV 2 to rapidly mutate and infect multiple cell types. Host inflammation and evasion of host immune responses by viruses are believed to play major roles in disease severity of human Corona viruses (hCoVs), thus uses of anti-inflammatory and immune-boosting agents apart from complete multi-disciplinary approach are suggested to combat the ranvaging SAR-hCOV 2 infection. This paper related the structural proteins and life cycle of CoV with host immune responses to CoV. This is to bring out gaps in knowledge for possible future researches